Minimum case volumes from the perspective of university providers - Krautz, Christian; Grützmann, Robert (Chirurg, 2022)
The association between patient volume and treatment quality has been sufficiently proven for certain surgical interventions (e.g., resections of the esophagus and pancreas). International experience shows that centralization of patient care in these fields leads to an improvement in outcome quality. If properly enforced, minimum caseload requirements can induce centralization effects in the hospital market. Overcapacities in the German hospital market and high nationwide in-hospital mortality rates (e.g., nationwide postoperative hospital mortality after esophageal and pancreatic resections) justify the current changes in the minimum caseload requirement regulation. Nevertheless, still open questions on volume-outcome relationships (e.g., additive volume effects of associated organ systems) have yet to be answered by scientific studies. In addition, the special role of university medical centers in the German healthcare system needs to be considered in the minimum caseload requirement regulation in order not to jeopardize the importance of university clinics in science, education and patient care through self-regulatory processes in the hospital market induced by minimum caseload requirements.
CRIS-Team WoS Importer:2022-03-25